SAT0151 Efficacy and safety of biologic therapy in elderly rheumatoid arthritis patients compared to young - a systematic review. (15th June 2017) - Dalal, D; Duran, J; Brar, T; Alqadi, R; Halladay, C; Lakhani, A; Rudolph, J
Abstract : Background: Rheumatoid arthritis (RA) patients are disproportionately older (33% >60 years). With improved biologic therapy for RA, there is a need to understand the efficacy and safety of biologic therapies in older RA (oRA) patients. Objectives: To systematically review published literature to summarize the available evidence of efficacy and safety of biologic agents in oRA compared to young RA (yRA) patients. Methods: A search in EMBASE, MedLine, Toxline, clinicaltrials.gov and Cochrane database was performed to identify clinical trials (RCT) and observational (OBS) studies of >6 months comparing the efficacy and safety of biologic agents in oRA relative to yRA. The biologics of interest were all anti-TNF agents, abatacept (ABA), tocilizumab (TCZ), rituximab (RTX) and tofacitinib (TOF). English language studies conducted in adult RA that reported age-associated outcomes were included. Studies assessing juveniles, inflammatory arthritis or not reporting older age outcomes were excluded. Safety outcomes included infections, adverse drug reactions (ADR), and malignancy. 2 independent rheumatologists reviewed abstracts, full text articles, and abstracted data from included articles. Conflicts were resolved by a 3rd reviewer. Abstracted data was summarized and evaluated for use within a meta-analysis Results: Of 5353 abstracts, 187 were identified for full text review and 32 articles were included in this review. Articles were focused on efficacy (n=9), safety (n=15), or both (n=8). Most articles (n=22; 69%) focused on anti-TNF agents, then TCZ (n=4), ABA (n=2), TOF (n=2), RTX (n=1) and all biologics (n=1). Most studies were OBS studies (n=28, 88%) and fewer (n=4) were post-hoc analyses of RCT. In total, 99947 unique patients were identified, of which ∼24% were older. Most studies used valid definitions of RA and outcomes; only 25% of the studies have <20% loss to follow up. There was heterogeneity in reporting outcomes and time of follow up. Out of the 12 efficacy studies focusing on anti-TNF agents, 9 (75%) showed a reduced efficacy in oRA on DAS28, HAQ, CDAI, SDAI, EULAR or ACR response scales relative to yRA. Studies focusing on TCZ (n=2) and RTX (n=1) also showed a reduced efficacy in oRA. OBS studies in ABA (n=2) showed comparable efficacy in oRA and yRA. Meta-analysis was limited by heterogeneity. Safety was the focus of anti-TNF (n=15), TCZ (n=3), 2 on TOF (n=2), 1 on ABA (n=1), RTX and all biologics (n=1) studies. Among these 23 safety studies, 74% (n=17) demonstrated worse safety outcomes in oRA. like in oRA. Of studies focusing on infection in anti-TNF agents, 82% (9 of 11) reported increased risk in oRA. Among the anti-TNF studies, 2 out of the 4 (50%) measured more ADR in oRA. A meta analysis of 4 studies reporting infectious outcomes in anti-TNF agents at >1 year found a pooled risk estimate was 1.59 (95% CI 1.45–1.76). Conclusions: There is heterogeneity within the literature of biological agents in RA, particularly when age is considered. Given the anticipated population increase in the oRA, there is an urgent need for analysis of these medications in oRA patients for both safety and efficacy. Disclosure of Interest: None declared